GEISHA : ANTARA TRADISI DAN CITRA BURUK - Titik Suliyati (KIRYOKU, 2018)
Known as a developed and modern country, Japan still preserves traditions imerged and developed since centuries ago. These unique traditions still exist and colour the life of modern Japanese society. One of these traditions that possesed the uniqueness is the life of Geisha . Up till now the life of Geisha is a misterious one and many Japanese people even do not want to know.            People outside Japan who do not understand the life of Geisha  and Japanese culture consider that Geisha  is like a whore. This idea is not entirely true although the profession of a Geisha  and a whore is to intertain  the guests who hire them. The difference between a Geisha  and a whore lies in their training : Geisha should  undergo special and phase by phase training. Unlike a whore that depends on her physical beauty and ability to make love, a Geisha not only posseses beautiful physic but she has to posses ability in some tradition ceremonies, conduct and  wide general knowledge. Bad impression toward a Geisha  is when she did mizuage. Mizuage is to give her virginity to a man that pays her highly.            In doing her duty a Geisha does not always give sexual service, but principally she intertain guests by singing, playing musical instrument, dancing, serving tea (cha-no-yu) and chatting with partner. A Geisha gives sexual service only to danna. Pricipally a Geisha can not be called a whore. Keywords : Geisha,Japanese tradition, bad image